Human Capital: its definition and scope in the Local and Regional Development - Navarro Abarzúa, Iván (Education Policy Analysis Archives, 2005)
This article describes and analyzes the concept of Human Capital nor in a mechanical way nor using the neo-liberal definitions, but by linking the theory with practice in an specific territorial analysis. This is about superseding global theoretical models of social analysis, which generally sub-utilize the empirical data provided by territorial analysis, often falling into unhelpful generalizations and abstractions. Furthermore, this analysis is not centered in establishing causality, and it aims to be a contribution in the development of a theory of Human Capital and its impacts in the regional and local development.